The specific effects of the pch1 resistance gene on the development of Oculimacula yallundae, the causing agent of wheat eyespot - Blein M.; Levrel A.; Gautier V.; Muranty H.; Barloy D. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The resistance gene Pch1 is widely used in wheat breeding but neither its function nor its role in the plant defence reaction are known. Its effects on the pathogen development were previously studied but the host genotypes used did not allow to discriminate the influence of Pch1 from the one of the genetic background. This is the first report highlighting the specific effects of the Pch1 gene on Oculimacula yallundae development. We compared the development of eyespot spores on wheat near isogenic lines (NILs) of which genetic backgrounds only differ by the presence or the absence of Pch1. We collected data on the main developmental stages of the pathogen: spore germination, secondary hyphae formation, appressoria formation, development of a mycelial network, latency period, infection mat formation and penetration. The Pch1 gene has no effect on the germination of spores. It rather seems to delay the development of the pathogen. In parallel to this work, we are also using the wheat NILs to carry out a functional analysis of the effects of Pch1 in the plant defence reaction.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)